Pengaruh Kompetensi, Kemampuan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai AMIK Citra Buana Indonesia Sukabumi - Marten Joni (JURNAL BUANA INFORMATIKA CBI, 2017)
Performance is the result of the quality of work accomplished by an employee in carriying out their duties in accordance with the responsibilities given to him, as you well know, there are some important factor that can determine the goals and improve organizational performance, namely competence, ability to work discipline. The purpose of this study was to determine the effect of simultaneous delivery of competence, ability to work and labor discipline on the performance of employees in Sukabumi AMIK Citra Buana Indonesia, to determine the effect of partial competence, ability to work and labor discipline on the performance of employees in Citra Buana Indonesia AMIK Sukabumi. This research method is a quantitave reseach studi that is based on data in the form of numbers-numbers that processed with statistical analysis for influence between variables and samples used are as many as 72 samples. Testing instrument to test the validity and reliability. Method of data analysis with statistic assisted management with SPSS (Statistic Package for Social Science). The results showed that the regression equation is obstained as follows : Y=0,731 + 0,465X1 + 0,230X2 + 0,092X3. Influence Competence (X1), the Ability to work (X2), and discipline (X3) joinly to employee performance (Y) is show by the regretion of X1, X2 dan X3 to Y at r = 0,859, meaning that the effect of competence (X10, ability ti work (X2), and Discipline (X3)to employee Performance (Y) very strong, and its influence + (positive) means higher competence (X1), the ability to work (X2), and Discipline (X3) is also increasing employee Performance (Y) in Citra Buana Indonesia AMIK Sukabumi.